The impact of the COVID-19 pandemic on physical therapy practice for people with multiple sclerosis: A multicenter survey study of the RIMS network - Kahraman, Turhan; Rasova, Kamila; Jonsdottir, Johanna; Medina, Carme Santoyo; Kos, Daphne; Coote, Susan; Tacchino, Andrea; Smedal, Tori; Arntzen, Ellen Christin; Quinn, Gillian; Learmonth, Yvonne; Pedulla, Ludovico; et al. (Multiple sclerosis and related disorders, 2022)
BACKGROUND: The impact of the COVID-19 pandemic on physical therapy services for people with multiple sclerosis (pwMS) is unknown. Therefore, the Special Interest Group for Mobility (SIG Mobility) of the European Network for Best Practice and Research in Multiple Sclerosis Rehabilitation (RIMS) has undertaken the initiative to examine the impact of the COVID-19 outbreak on physical therapy services and physical activity participation in pwMS across Europe, Israel and Australia. OBJECTIVE: To describe the impact of the COVID-19 outbreak on physical therapy practice from the perspective of the therapist. METHODS: An online survey was developed and conducted from December 2020 to July 2021. The survey (50 questions), included multiple-choice questions and open-ended responses. RESULTS: In total, 215 physical therapists (PT's) from 9 countries (Australia, Belgium, the Czech Republic, Ireland, Israel, Italy, Norway, Spain, and Turkey) participated in the study. The therapy most affected during the pandemic was aerobic training/conditioning exercises; 33.5% reported that these activities were either reduced or unavailable. In contrast, 15% of the PTs reported increased use of relaxation/mind body techniques and/or fatigue management programs during the pandemic. PTs reported a mixture of positive and negative feelings about the therapeutic sessions offered during the pandemic. Most reported positive feelings included "positive" (26.5%), and "optimistic" (24.7%). Negative feelings most frequently reported included "worried" (30.7%), and "hesitant" (20.9%). The PTs reported a 10% decrease in the use of hands-on techniques and a 10% increase in the use of oral instructions when treating moderately and severely pwMS during as compared to before the pandemic. CONCLUSION: The COVID-19 pandemic has affected physical therapy services in pwMS internationally in terms of content, frequency of use and format.
Keywords: pandemie; RIMS; Physical therapy; International network; lidé; průzkumy a dotazníky; Multiple Sclerosis; Multiple sclerosis; Physical Therapy Modalities; techniky fyzikální terapie; Surveys and Questionnaires; Pandemics; roztroušená skleróza; COVID-19; Humans